Fungal resistance mediated by maize wall‐associated kinase ZmWAK‐RLK1 correlates with reduced benzoxazinoid content. Issue 2 (4th September 2018) - Yang, Ping; Praz, Coraline; Li, Beibei; Singla, Jyoti; Robert, Christelle A. M.; Kessel, Bettina; Scheuermann, Daniela; Lüthi, Linda; Ouzunova, Milena; Erb, Matthias; Krattinger, Simon G.; Keller, Beat
Summary: Wall‐associated kinases (WAKs) have recently been identified as major components of fungal and bacterial disease resistance in several cereal crop species. However, the molecular mechanisms of WAK‐mediated resistance remain largely unknown. Here, we investigated the function of the maize gene ZmWAK‐RLK1 ( Htn1 ) that confers quantitative resistance to northern corn leaf blight (NCLB) caused by the hemibiotrophic fungal pathogen Exserohilum turcicum . ZmWAK‐RLK1 was found to localize to the plasma membrane and its presence resulted in a modification of the infection process by reducing pathogen penetration into host tissues. A large‐scale transcriptome analysis of near‐isogenic lines (NILs) differing for ZmWAK‐RLK1 revealed that several differentially expressed genes are involved in the biosynthesis of the secondary metabolites benzoxazinoids (BXs). The contents of several BXs including DIM2 BOA‐Glc were significantly lower when ZmWAK‐RLK1 is present. DIM2 BOA‐Glc concentration was significantly elevated in ZmWAK‐RLK1 mutants with compromised NCLB resistance. Maize mutants that were affected in overall BXs biosynthesis or content of DIM2 BOA‐Glc showed increased NCLB resistance. We conclude that Htn1 ‐mediated NCLB resistance is associated with a reduction of BX secondary metabolites. These findings suggest a link between WAK‐mediated quantitative disease resistance and changes in biochemical fluxes starting with indole‐3‐glycerol phosphate.